Developing English Learning: An Innovative Online Instructional Model with an Inquiry-Based Approach - Syakur, Abd; Sutama, Sutama; Sutopo, Anam; Prasetya, Rizki; Prawoco, Fajar Sandi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research and development (R&D) activity aims to develop a reliable, practical, and effective inquiry learning model that includes preliminary research, product design and development, and assessment. In this development process, the stages outlined by Plomp and Nieveen are adopted. Forty pharmacy students from the pharmacy study program of a state university in Malang, East Java, took part in learning during the 2021-2022 academic year. A questionnaire with Likert Scale 4 categories is a research tool. The expert validation test revealed that "Eligible" is the average result of the validator's assessment criteria. It is possible to immediately implement product results that reach 90.25% on developed media and 89.60% for digital teaching materials with interactive digital flip-book concepts. In terms of the practicality of the products developed, the average V values achieved were 0.86, 0.92, and 0.85, respectively. The results of hypothesis testing in the implementation show that Sig. value (Sig. (2-tailed)) was 0.002, which is smaller than the 0.05 significance level. Accordingly, the research findings confirm a notable improvement in students' critical thinking and problem-solving skills through the implementation of the inquiry learning model through multimedia.